The Effect of Parental Attachment on Adolescent Social Emotional Health - Amseke, Fredericksen Victoranto (LPPM Universitas 17 Agustus 1945 Samarinda, 2025)
Social emotional health is essential for adolescents to develop positive competencies both physically and psychologically. Social emotional health is influenced by parental attachment as an external factor. The purpose of this study was to determine the effect of parental attachment on the social emotional health of adolescents as students. This study was conducted at Institut Agama Kristen Negeri Kupang with a total of 185 adolescents who were students in the first semester of 2022. This study used quantitative research methods. This research instrument uses a social emotional health scale compiled by Furlong, et al (2016) called social emotional health higher education while he parental attachment scale made by Armsden and Greenberg (2009) from the IPPA/Inventory of Parent and Peer Attachment theory. The results of this study found there was a positive and significant effect of parental attachment on adolescent social emotional health with p = 0.000 and F = 89.986, R square = 0.330. Father's attachment has a contribution to adolescent social emotional health by 15% while mother's attachment to adolescent social emotional health is 18% so that overall parental attachment both father and mother has a contribution to adolescent social emotional health as a student by 33%. It is expected that adolescents can establish an attachment relationship with parents both father and mother to improve positive social emotional health.